Chemokine CXCL13 expression was up-regulated in Clostridium difficile infection. (December 2016) - Wang, Lifang; Cao, Ju; Li, Congya; Zhang, Liping
Highlights: Serum and fecal CXCL13 levels were significantly enhanced in patients with CDI. Serum CXCL13 was significantly correlated with clinical parameters. CXCL13 mRNA and protein were increased in Clostridium difficile infection mouse model. CXCL13 may be a potential new diagnostic and prognostic biomarker for CDI. Abstract: Clostridium difficile infection (CDI) is the leading cause of antibiotic- and healthcare-associated diarrhea. CXCL13 is a well-known CXC chemokine involved in inflammation, but its role in CDI remains unknown. In this study, serum and fecal samplings were collected from 51 CDI patients, 50 diarrhea patients without CDI and 50 healthy control subjects to determine the CXCL13 levels by enzyme-linked immunosorbent assay (ELISA). Besides, a mouse model of C. difficile infection was established, and murine serum and colon tissues were collected for detection of CXCL13 expression using quantitative real-time RT-PCR, ELISA, Western blot, or immunohistochemistry. We found that CXCL13 concentration in serum and fecal samples from CDI patients was significantly higher compared with that from diarrhea patients without CDI and that from healthy controls. Elevated serum CXCL13 positively and significantly correlated with blood markers of inflammation and yielded an increased area under the ROC curve of 0.929. In murine C. difficile infection, CXCL13 were also dramatically increased in serum and infected colon tissues at the transcriptional and protein levels. The elevated CXCL13 levels positively and significantly correlated with inflammatory scores. Therefore, CDI is associated with enhanced release of CXCL13. This study indicated that CXCL13 may be pathogenically involved in CDI and served as a potential new biomarker for diagnosis and prognosis in CDI.